If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1(2z + -4) = 2 + -3z Reorder the terms: 6 + -1(-4 + 2z) = 2 + -3z 6 + (-4 * -1 + 2z * -1) = 2 + -3z 6 + (4 + -2z) = 2 + -3z Combine like terms: 6 + 4 = 10 10 + -2z = 2 + -3z Solving 10 + -2z = 2 + -3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '3z' to each side of the equation. 10 + -2z + 3z = 2 + -3z + 3z Combine like terms: -2z + 3z = 1z 10 + 1z = 2 + -3z + 3z Combine like terms: -3z + 3z = 0 10 + 1z = 2 + 0 10 + 1z = 2 Add '-10' to each side of the equation. 10 + -10 + 1z = 2 + -10 Combine like terms: 10 + -10 = 0 0 + 1z = 2 + -10 1z = 2 + -10 Combine like terms: 2 + -10 = -8 1z = -8 Divide each side by '1'. z = -8 Simplifying z = -8
| 1.5x^2=0 | | 10x-8+3x-5=9x-3+3x | | 35-47=-3x+10x-6x | | 7x^2=64 | | log(x)+log(x-11)=log(10x) | | x/2-3-x=1 | | x^2+10x-45=0 | | 3(x+6)-6(3x+6)=-16(x+3)+2 | | 36-24/6x2 | | 1/3x^2-3 | | 10+x/6=-20 | | ((x-2y)/(15y)-(3)/(15y)) | | 8+11x=0 | | 1/6d=51 | | b^2+4b-16=0 | | ((1/3)5x+3)-((1/4)x+5)=4 | | 1/6d=15 | | d+2e=f | | 4.17x+49=17.3889+7x | | an=3n+1 | | x^3-9x-6=0 | | 2(3y-9)=5y+-9 | | 2[x/4+7]=18 | | 3y-x=-9 | | (4x-28)/3=(3x+21)/4 | | 6z-14=9z+5 | | x+16+11=33 | | 4(13/4)+2y-5 | | 3/4x-1/2=10 | | 7x-2=41 | | (x+6)(x+6)=49 | | (y-8)(y-8)-28=0 |